2004
DOI: 10.1002/zoo.20022
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy detection and fetal monitoring via ultrasound in a giant panda (Ailuropoda melanoleuca)

Abstract: Transabdominal ultrasound was used to monitor the reproductive tract of a female giant panda (Ailuropoda melanoleuca) for three consecutive breeding seasons starting in 2001. Parturition did not occur in 2001 or 2002. In 2003, uterine enlargement was noted 109 days after natural mating occurred. A twin pregnancy was detected via transabdominal ultrasound 134 days following natural mating. Four subsequent ultrasound examinations, performed at 137, 138, 140, and 142 days postmating, documented fetal development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…Secondly, and perhaps more importantly, giant pandas may be experiencing significant embryonic loss, with many females previously classified as 'pseudopregnant' actually undergoing failed pregnancies (Steinman et al 2006). For example, Sutherland- Smith et al (2004) documented two foetuses during late gestation (day 134) via ultrasound in a female that later gave birth to a single cub (day 150). Anecdotal reports of suspicious foetal loss via ultrasonographic examinations have also been noted at the Smithsonian's National Zoological Park (S Murray, personal communications) and Memphis Zoo (A J Kouba, personal communications).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, and perhaps more importantly, giant pandas may be experiencing significant embryonic loss, with many females previously classified as 'pseudopregnant' actually undergoing failed pregnancies (Steinman et al 2006). For example, Sutherland- Smith et al (2004) documented two foetuses during late gestation (day 134) via ultrasound in a female that later gave birth to a single cub (day 150). Anecdotal reports of suspicious foetal loss via ultrasonographic examinations have also been noted at the Smithsonian's National Zoological Park (S Murray, personal communications) and Memphis Zoo (A J Kouba, personal communications).…”
Section: Discussionmentioning
confidence: 99%
“…For years, a compliment of non-invasive tools has been used to approximate the reproductive status of female giant pandas in ex situ collection, including through behavioural observations (Czekala et al 1998, McGeehan et al 2002, urinary hormone quantification (Steinman et al 2006), visual changes of the vulva (McGeehan et al 2002), vaginal cytology and/or ultrasonography in cooperative individuals (Sutherland-Smith et al 2004, Zhang et al 2009). Urinary progestagen monitoring has been especially useful for tracking pregnancy (or pseudopregnancy) of captive mated and/or artificially inseminated females.…”
Section: Discussionmentioning
confidence: 99%
“…This physiological response is believed to be seasonal and could be an adaptation to an unpredictable food source that would make it advantageous for the birth of the offspring to match a time of highest availability of food sources (Mead 1989, Sandell 1990. One ultrasound study on a single animal suggested that delayed implantation might occur in giant pandas (Sutherland-Smith et al 2004), but this has not yet been confirmed in other pandas.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is perhaps that pregnancy has been notoriously difficult to detect in giant pandas in part because they gain little weight and their fetuses develop late (Sutherland-Smith et al 2004). In the past, captive managers were often unable to detect a female's pregnancy status until days before the birth, with pseudopregnancies often reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation